Real-world eye-tracking in face-to-face, web and SAQ modes - Olena Kaminska; Tom Foulsham (University of Essex, Institute for Social and Economic Research (ISER), 2013)
Eye-tracking is becoming a popular testing tool to understand how different forms of asking questions influence respondents' answers. Until now, due to the ease of eye-tracking on PC, this method has almost exclusively been used to test questions in web/PC mode. Our paper extends the application of eye-tracking to other modes with a visual component, including self-administered paper and pencil (SAQ) and face-to-face with show-cards (PAPI) in a realistic interview set up. The current article reports on a feasibility study of using a real-world eye-tracker to measure visual attention in the modes with visual component.
Keywords: C81; C83; 330; eye-tracking; mode effect; primacy effect; show cards